Catalytic hydrogenation of nitrocyclohexane as an alternative pathway for the synthesis of value-added products. Issue 18 (9th August 2022) - Kowalewski, Emil; Śrębowata, Anna
Abstract : Catalytic hydrogenation of nitrocyclohexane could be an alternative source of various useful chemicals: cyclohexanone oxime, cyclohexanone, cyclohexanol, cyclohexylamine and dicyclohexylamine. Abstract : Catalytic hydrogenation of nitrocyclohexane could be an alternative source of various useful chemicals: cyclohexanone oxime, cyclohexanone, cyclohexanol, cyclohexylamine and dicyclohexylamine. Each one of these compounds found application in the modern chemical industry and has been produced on a large scale in multi-step processes. The possibility of direct synthesis via selective hydrogenation of nitrocyclohexane seems to be an excellent alternative. A thorough literature review shows broad research potential in this topic. Herein, we present the state of the art on nitrocyclohexane hydrogenation under batch and flow conditions and indicate possible directions for further studies in this topic.